Analisis Efektifitas Mesin Pewarna Serat Optik Dengan Metode Overall Equipment Effectiveness (OEE) (Studi Kasus PT. Voksel Electric Tbk.) - Ilham Saharani; Sukanta Sukanta (Universitas Indraprasta PGRI Jakarta, 2021)
To support the manufacturing system, the performance of the equipment used must be considered so that it can be used properly. PT. Voksel Electric Tbk. is a company engaged in the electricity and telecommunications industry. The production process of PT. Voksel Electric Tbk. inseparable from production tools or machines that have time and performance availability and are ready to fulfill company orders. One of the tools to measure the effectiveness of a machine is to use Overall Equipment Effectiveness (OEE), which has been recognized worldwide to measure machine effectiveness. The purpose of this study is to determine the level of effectiveness of the CETC 02 Coloring FO machine in the coloring line and its causes so that the company can make the right decision to fix it based on the results obtained. With 67% availability, 95% performance level, and 100% quality level, the total effectiveness of the entire machine in one work shift for 11 days from January 14 2020 to January 29 2020 is 63% which is above the fairness limit of the Japan Institute benchmark standard. of Plant Management (JIPM), namely 60%. The availability level accounts for the smallest percentage because it is caused by many things that require the machine to stop, whether intentional or unintentional, such as on January 22, 2020, the greatest downtime was recorded at 360 minutes because at that time the machine had a problem and could not be operated before it was handled by the maintenance department.